2004
DOI: 10.1016/j.conb.2004.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Spider mechanoreceptors

Abstract: Spiders have highly developed mechanosensory systems, some of which provide access to forms of stimulation alien to our own sensations. Studies of hair-shaped air movement detectors (trichobothria) and tactile sensors have uncovered an outstanding refinement of the processes of stimulus uptake and stimulus transformation, which reflect details of both stimulus physics and behavioral significance. They also emphasize the potential contained in the seemingly simple Bauplan of arthropod cuticular hairs. Embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 0 publications
3
130
0
Order By: Relevance
“…Many of these hairs are mechanoreceptors, some of which are chemosensory (3,7). In several groups, such as crustaceans, arachnids, and insects, many of these mechanoreceptors serve as fluid flow sensors.…”
Section: Diversity Of Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these hairs are mechanoreceptors, some of which are chemosensory (3,7). In several groups, such as crustaceans, arachnids, and insects, many of these mechanoreceptors serve as fluid flow sensors.…”
Section: Diversity Of Structuresmentioning
confidence: 99%
“…In orthopterid insects, the location of flow-sensing hairs is mainly at the rear end of the abdomen (specifically on the cerci), thereby providing useful flow information about predators approaching from behind. In spiders and crayfish, they are mainly found on the front (forelegs and antennules) and posterior (hindlegs and tailfan) appendages of the body, serving as detectors of both prey and predators (3,74). In marine copepods, they are located on the antennules, allowing these animals to scan the environment at a distance from their bodies (27).…”
Section: Diversity Of Structuresmentioning
confidence: 99%
“…The particle velocity component of a sound wave, quantified by the magnitude and direction of the harmonic oscillations of the particles within a fluid, is detected by many organisms through the displacement of arrays of flagellar receivers, for example, the trichobothria on spiders (Barth, 2004) and cilia on cricket cerci (Shimozawa et al, 2003), or indeed bilateral flagellar ears as found in mosquitoes (Clements, 1999) and fruit flies such as Drosophila (Ewing, 1978;Manning, 1967). Drosophila melanogaster use bilateral antisymmetric antennae to receive the particle velocity component of an acoustic stimulus (Ewing, 1978;G枚pfert and Robert, 2001;G枚pfert and Robert, 2002;Manning, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that two geometric features of vibrissae grant them the multimodal capacity evolutionarily denied to arthropod hairs: (1) vibrissae are much longer than arthropod hairs; and (2) each vibrissa is held tightly at its base (Bagdasarian et al, 2013), whereas arthropod flow-sensing hairs are held loosely by a socket (Barth, 2004).…”
Section: The Mechanics Of Airflow Versus Touchmentioning
confidence: 99%